Upaya Layanan Bimbingan dalam Meningkatkan Disiplin dan Perilaku Positif Siswa Kelas V SDN 58 Baubau - Adel, Adel; Anju Sanjena; Mika Nultisari; Berlian Putri Saudjana; Dawis, Dawis; Haliadi Haliadi (FKIP UNSULTRA, 2026)
This study aims to describe the implementation and analyze the effectiveness of guidance use of gadgets or the phenomenon of staying up late, as well as minor services in improving discipline and positive behavior of fifth-grade students at SDN 58 Baubau. The main problems found in the field are low student learning concentration due to excessive disciplinary violations such as arriving late. This study uses a qualitative approach with a case study design to explore the phenomenon in depth. Data were collected through in-depth interviews with class teachers and students, direct participant observation, and documentation studies. Data analysis techniques follow the interactive model of Miles and Huberman which includes data reduction, data presentation, and drawing conclusions. The results show that the implementation of guidance services is carried out holistically by prioritizing the instillation of manners and morals before knowledge, intensive collaboration with parents, and practical interventions in the classroom proved very effective in improving student discipline. Significant behavioral changes are seen in increased punctuality in attendance, responsibility in carrying out cleaning duties, and students' ability to focus during the learning process without disturbing their peers in class.